PERANAN WORLD WIDE FUND FOR NATURE (WWF) DALAM KONSERVASI TAMAN NASIONAL TESSO NILO (TNTN) - Hutabalian, Eva Yeni; Jamaan, Ahmad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
This research describes the land and forest fires that have large impact on a various sectors, such as the economy, transportation, agricultural production, the level of public health and state relations. Tesso Nilo National Park area suffered damage alarming various parties, including the Non-Government Organizations (NGO) and International Government Organizations (IGOs). The state of Tesso Nilo National Park has changed completely as a result of the increase in economic activity of the local population. This environmental issue is not just domestic problem of Riau administration or Indonesian government, but also being international community concern.To analyze the research question, the writer uses constructivism. Constructivism assumes that shared ideas and values form the identity (ideational identity), which in turn affects interest. Ideational identity and interests is what ultimately helped determine political action. Constructivism gives attention to the importance and existing public discourse in society because discourse reflects and form beliefs and interests, and maintain norms that underlie the community acted.This research shows WWF role in the establishment of conservation areas Tesso Nilo National Park, beginning with cooperation with stakeholders including BKSDA Riau, Riau provincial government in this case the Riau Provincial Forestry Office, District Government in this case the District Forestry Office Riau province, local people and various companies that operating in related areas.Keyword: conservation, degradation, illegal logging, Non-Governmental Organization